Analisis Potensi Unggulan Kabupaten Kepulauan Yapen dalam Menopang Pembangunan Provinsi Papua Tahun 2004-2008 - Agus Tri Basuki (Unisia, 2009)
Regency Kepulauan Yapen is a new regency as a result of regional separation and islocated in the area which is very closely to the neck of the bird head of Papua Province. Aneconomic development strategy of a region must be able to identify all economic potenciesof the region. Using analyses of MRP, Shift Share, LQ, Overlay and Klassen Typology,this research explores the economic potencies of Regency Kepulauan Yapen. This researchreveals that the Regency has economic advantages in most sectors, except thoseof mining and manufacturing industries. The most advantageous sectors are those ofservices, finance, service companies, and construction. Other advantageous sectors arethose supporting tourist industries, such as trade, hotel and restaurants.Keywords: economic development, economic potencies, advantages.